2009
DOI: 10.1177/1059601108331217
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Supervision and Employee Emotional Exhaustion

Abstract: The authors examined the relationship between subordinates' core self-evaluations and supervisors' abusive supervision. Furthermore, they examined whether subordinates' perceived coworker support and subordinates' susceptibility to emotional contagion moderated the relationship between supervisors' abusive supervision and subordinates' emotional exhaustion. They analyzed data from 290 subordinates who had immediate supervisors using hierarchal multiple regression. Results show that core self-evaluations were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
163
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(189 citation statements)
references
References 64 publications
13
163
0
2
Order By: Relevance
“…Consistent with previous findings (e.g., Wu & Hu, 2009), employees who perceive high coworker knowledge sharing may not have a positive psychological experience but instead may face dissonance in the context of highly abusive supervision. Since employees receive different treatments from the key actors, they may deplete their self-resources, which in turn may limit the benefits of coworker knowledge sharing.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with previous findings (e.g., Wu & Hu, 2009), employees who perceive high coworker knowledge sharing may not have a positive psychological experience but instead may face dissonance in the context of highly abusive supervision. Since employees receive different treatments from the key actors, they may deplete their self-resources, which in turn may limit the benefits of coworker knowledge sharing.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the positive relationship between abusive supervision and employee deviance was stronger when distributive justice was high rather than when it was low (Thau & Mitchell, 2010). Wu and Hu (2009) also found that the relationship between abusive supervision and emotional exhaustion was strengthened when coworker social support was high rather than when it was low. Applying this argument to our study, although coworker knowledge sharing may provide valuable resources, employees who face inconsistent information (high abusive supervision in this study) may find it difficult to get the full benefit of coworker knowledge sharing, due to their lack of self-resources.…”
Section: The Boundary Conditions Of General Self-efficacy and Abusivementioning
confidence: 87%
See 3 more Smart Citations